Experimental study of heat transfer natural convection in horizontal internally finned tube - Mohd Waqiuddin, Nordin (2009)
A simplified model of the tube heat exchanger is used to experimentally study the thermal impact of using four internal fins fixed to the diameter inside tube heat exchanger. This model consists of a heated horizontal cylinder with a constant heat flux placed around the cylinder. The project also using the laminar air flow as the medium in the tube. Correlations for the averaged Nusselt number for different configuration are presented. These correlations relate the averaged Nusselt number with the variation of tube with fins and without fins (smooth), and different Raleigh numbers. The fins are used to increase the area inside the tube to relate with heat transfer area. It is found that, unlike expected, the value of Nu for horizontal cylinder under constant heat flux conditions varies with the variation of the heat flux. Also it is found that the value of Nu increases as the area inside cylinder increases. To be conclusive on this result a further experimentations are needed. The experimental result are expected to be very useful for the design of pipelines and heat exchanger tube for more efficient.